Smart Nanorods for Highly Effective Cancer Theranostic Applications. Issue 6 (27th December 2013) - Yang, Yinlong; Zhang, Xiujuan; Yu, Caitong; Hao, Xiaojun; Jie, Jiansheng; Zhou, Mengjiao; Zhang, Xiaohong
<x xml:space="preserve">Abstract</x> Combination of chemotherapy and photothermal therapy is considered to be a promising strategy for the next generation of cancer treatments. However, it has been limited by difficulties in obtaining high drug payload chemo‐photothermal agents, and thus complete destruction of tumor without recurrence has never been achieved, unless they are conjugated with some targeting ligands for special targeted drug delivery. Herein, iron oxide nanoparticle (IONP)‐doped 10‐hydroxycamptothecin drug nanorods (HCPT NRs), with an organic conducting polymer poly(4‐styrenesulfonate) (PEDOT) coating outside, are developed for cancer diagnosis and chemo‐photothermal therapy. The drug‐loading capacity of HCPT in the complex NRs reaches up to 72%, which is much higher than previously reported carrier‐based nanocomposites. In vitro studies show that the resulting NRs demonstrate an excellent chemo‐photothermal synergistic effect for tumor ablation. More importantly, 100% in vivo tumor elimination is achieved under a low laser power density of 1 W cm−2 without weight loss and tumor recurrence. Moreover, IONP endow these drug nanocomposites with imaging capabilities, thus rendering the resulting HCPT‐PEDOT NR an all‐in‐one processing system for diagnosis and treatment with low systematic toxicity.